Laporan Keuangan PT Garuda Indonesia Sebagai Alat Evaluasi Kinerja Keuangan dalam Industri Penerbangan (Lembaga Pengembangan Kinerja Dosen, 2025)
Garuda Indonesia, as the national airline, has a strategic role in supporting connectivity and economic growth in Indonesia. In recent years, the company has experienced significant financial pressure due to the pandemic, high operational costs, and dependence on external financing. This study evaluates Garuda Indonesia's financial performance through an analysis of its 2022 and 2023 financial statements, focusing on liquidity, profitability, and solvency indicators. Using a quantitative descriptive approach, data is analyzed through financial ratios and trend comparisons. The results of the study show that although the company recorded a net profit in 2023, most of the profit came from non-operational items, while cash flow and equity actually decreased further. These findings indicate that the financial recovery process is still fragile and highly dependent on temporary adjustments. This study emphasizes the importance of a more comprehensive restructuring strategy and provides practical implications for managerial decision-making, as well as being a relevant reference for academic studies in the field of aviation sector financial management.